2018
DOI: 10.1057/s41262-018-0132-2
|View full text |Cite
|
Sign up to set email alerts
|

The levers of engagement: an exploration of governance in an online brand community

Abstract: Titl eTh e Lev e r s of E n g a g e m e n t: An Ex plo r a tio n of Gov e r n a n c e in a n O nlin e B r a n d Co m m u ni ty Typ e Articl e U RL h t t p s:// u al r e s e a r c h o nli n e. a r t s . a c. u k/id/ e p ri n t/ 1 4 6 3 4/ D a t e 2 0 1 9Cit a tio n Coo p er, Tony a n d S t a v r o s, Co n s t a n ti n o a n d Do b el e, Ang el a (2 0 1 9) T h e Lev e r s of E n g a g e m e n t: An Ex plo r a tio n of Gov e r n a n c e in a n O nli n e Br a n d Co m m u ni ty. Jou r n al of B r a n d M a n a g e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 60 publications
(63 reference statements)
1
36
1
Order By: Relevance
“…Online brand-enabled relationships can flourish in many platforms, including social media, primarily Facebook -where most online brand-enabled relationship research is conducted, but also on Twitter, Pinterest, and Google+ (Habibi et al, 2014), travel sites as TripAdvisor (Nguyen et al, 2015;Azer and Alexander, 2018;Bigné et al, 2019), trading platforms, such as eBay (Dholakia et al, 2009;Nguyen et al, 2013), general company web pages (Thorbjørnsen et al, 2002), dedicated brandcommunity websites (Casaló et al, 2007) and online forums (Cova and White, 2010;Cooper et al, 2019).…”
Section: Brand Initiated Relationships In the Virtual World And Research Focusmentioning
confidence: 99%
“…Online brand-enabled relationships can flourish in many platforms, including social media, primarily Facebook -where most online brand-enabled relationship research is conducted, but also on Twitter, Pinterest, and Google+ (Habibi et al, 2014), travel sites as TripAdvisor (Nguyen et al, 2015;Azer and Alexander, 2018;Bigné et al, 2019), trading platforms, such as eBay (Dholakia et al, 2009;Nguyen et al, 2013), general company web pages (Thorbjørnsen et al, 2002), dedicated brandcommunity websites (Casaló et al, 2007) and online forums (Cova and White, 2010;Cooper et al, 2019).…”
Section: Brand Initiated Relationships In the Virtual World And Research Focusmentioning
confidence: 99%
“…Inspired by management research, we distinguish two types of community climate: controlling and supportive [11]. Although research has revealed that organizations with a supportive climate encourage members to participate, exchange their information, and practice constructive conflict resolutions openly and freely [12], participants may perceive the community to be unsafe without proper control [13]. However, little research has examined the effect of a controlling climate in an OBC context.…”
Section: Introductionmentioning
confidence: 99%
“…To calculate customer engagement, we have adapted Rakhmawati et al (2018) Engagement Index (Rakhmawati et al, 2018) according to findings of Bitiktas et al, 2020;Cho et al, 2014;Cooper et al, 2019;Swani et al, 2014, that sharing, in terms of the extent of involvement is the highest form of engagement followed by commenting and liking. Also, we have decided to distinguish simple Likes from Love, Haha, Wow, Sorry, Anger types of "Likes."…”
Section: Aim Methodology and Methodsmentioning
confidence: 99%
“…In this context, we consider sharing, in terms of the extent of involvement, as the highest form of engagement followed by commenting and liking (Bitiktas et al, 2020;Cho et al, 2014;Cooper et al, 2019;Swani et al, 2014). Higher active or passive customer participation (customer engagement) with contents at least leads to better spreading the company messages, create better customer experience (Chiang et al, 2018), by enhancing relationships (De Vries et al, 2014), and increasing customers' value (Ersoy et al, 2018).…”
Section: Short Theoretical Backgroundmentioning
confidence: 99%